Polyetheretherketone Implants for the Repair of Large Cranial Defects: A 3-Center Experience. Issue 5 (27th June 2014) - Rosenthal, Guy; Ng, Ivan; Moscovici, Samuel; Lee, Kah K.; Lay, Twyila; Martin, Christine; Manley, Geoffrey T.
Abstract: BACKGROUND: Calvarial reconstruction of large cranial defects following decompressive surgery is challenging. Autologous bone cannot always be used due to infection, fragmentation, bone resorption, and other causes. Polyetheretherketone (PEEK) is a synthetic material that has many advantages in cranial-repair surgery, including strength, stiffness, durability, and inertness. OBJECTIVE: To describe our experience with custom-made PEEK implants for the repair of large cranial defects in 3 institutions: San Francisco General Hospital, Hadassah-Hebrew University Hospital, and the National Neuroscience Institute, Singapore. METHODS: A preoperative high-resolution computed tomography scan was obtained for each patient for design of the PEEK implant. Cranioplasty was performed via standard technique with the use of self-tapping titanium screws and miniplates. RESULTS: Between 2006 and 2012, 66 cranioplasties with PEEK implants were performed in 65 patients (46 men, 19 women, mean age 35 ± 14 years) for repair of large cranial defects. There were 5 infections of implants and 1 wound breakdown requiring removal of the implant (infection and surgical removal rates of 7.6% and 9.1%, respectively). Two patients required drainage of postoperative hematoma (overall surgical complication rate, 12.7%). Nonsurgical complications in 5 patients included seizures, nonoperative collection, and cerebrospinal fluid rhinorrhea that resolved spontaneously. Overall median patient or family satisfaction with the cranioplasty and aesthetic result was good, 4 on a scale of 5. Temporal wasting was the main aesthetic concern. CONCLUSION: Custom-designed PEEK implants are a good option for patients with large cranial defects. The rate of complications is comparable to other implants or autologous bone. Given the large size of these defects, the aesthetic results are good.